2021
DOI: 10.1016/j.psj.2021.101391
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a quillaja and yucca combination on performance and carcass traits of coccidia-vaccinated broilers exposed to an enteric disease challenge

Abstract: A series of 6 floor pen trials was conducted to determine the effects of a quillaja and yucca combination product on the performance and carcass traits of growing broiler chickens vaccinated for coccidiosis at the hatchery. In each of the trials graded levels (0, 250, and 500 ppm) of a quillaja and yucca combination ( QY ) were fed to Ross 708 broilers for the duration of each 42 d test. Trials were arranged in completely randomized block designs involving a minimum of 11 blocks per tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…An example is a combination of quillaja and yucca that contain saponins and are often used to promote intestinal health and immunity in poultry ( Bafundo et al, 2020 ). In a series of studies they were shown, in addition to improving gut health, to have beneficial effects against infections with Eimeria species, necrotic enteritis, and improve the effectiveness of live coccidiosis vaccines ( Bafundo et al, 2021a , b ). Synergism has been claimed for a 1:1 mixture of the natural alkaloid berberine and amprolium ( Malik et al, 2016 ).…”
Section: Anticoccidial Drugs Used In Combinationsmentioning
confidence: 99%
“…An example is a combination of quillaja and yucca that contain saponins and are often used to promote intestinal health and immunity in poultry ( Bafundo et al, 2020 ). In a series of studies they were shown, in addition to improving gut health, to have beneficial effects against infections with Eimeria species, necrotic enteritis, and improve the effectiveness of live coccidiosis vaccines ( Bafundo et al, 2021a , b ). Synergism has been claimed for a 1:1 mixture of the natural alkaloid berberine and amprolium ( Malik et al, 2016 ).…”
Section: Anticoccidial Drugs Used In Combinationsmentioning
confidence: 99%
“…; however, Enterococcus faecalis growth was inhibited by the antibiotics and by Yucca schidigera. Bafundo et al [55] observed reductions in mortality of broiler chickens, reduced numbers of fecal Clostridia, and decreased percentages of broiler chickens with Salmonella when treated with a product obtained from Quillaja saponaria trees and Yucca schidigera plants. In another study, Yucca schidigera additions to the litter of broiler chickens did not influence total colony counts of Enterobacteriaceae, yeast, mold, pH, moisture, or ammonia-N [56].…”
Section: Influence Of Yucca Schidigera On the Growth Microorganisms O...mentioning
confidence: 99%
“…Bafundo et al [55] examined disease response in broiler chickens given a product of Quillaja saponaria trees and Yucca schidigera plants. They observed reductions in mortality of birds and reductions in numbers of fecal Clostridia and Salmonella colonization.…”
Section: Influence Of Yucca Schidigera On Microbial and Fermentation ...mentioning
confidence: 99%
“…According to the number of sugar residues, aglycones are divided into monodesmosidic (one sugar residue), bidesmosidic (two sugar residues), and polydesmosidic saponins (three or more sugar residues) [17]. Plant saponins have a variety of biological activities, including immune regulation, anti-inflammatory, and hypoglycemic effects [18]. The potential immunomodulatory effects of saponins have attracted great attention since their discovery in 1925 as enhancers of the body's immune response to diphtheria or tetanus [19].…”
Section: Introductionmentioning
confidence: 99%